Chagall jawny i ukryty - Ruth, Dorot (Studia Europaea Gnesnensia, 2016)
In this paper, the authors chooses the theory of metarealism as a tool to reveal the worlds of Marc Chagall - the physical and metaphysical ones which function simultaneously. The purpose behind it is to help readers discover Chagall’s magical, mysterious and mystical environments which he so adroitly conveyed via his colourful creations. For this end, I analyzed three of his well-known paintings, each of which helped uncover his world of harsh reality merged with his life of fantasy, both spiced with symbolism.